An anatomy of the Spanish current account adjustment: The role of permanent and transitory factors - Mar Delgado-Téllez; Enrique Moral-Benito; Francesca Viani (SERIEs - Journal of the Spanish Economic Association, 2020)
This paper investigates how much of the current account adjustment after the global financial crisis in Spain can be explained by cyclical factors. For this purpose, we extend the IMF's external balance assessment methodology to allow for country-specific slopes and intercepts. The good fit of these cross-country regressions implies negligible residuals for most countries, and, as a result, the positive analysis of current account decompositions provides a more informative assessment of the external balance drivers. According to our findings, around 60% of the 11 pp. adjustment of the Spanish external imbalance over the years 2008-2015 can be explained by transitory factors such as the output gap, the oil balance, and the financial cycle-a share that diminished down to 50% during the more recent recovery period. The remaining adjustment of the Spanish external balance is explained by factors such as the cyclically adjusted fiscal consolidation, population ageing, lower growth expectations, or competitiveness gains, which can all be considered as more permanent phenomena.
Keywords: F21; F32; F41; 330; Current account; External adjustment; Global imbalances